Shaping Young Minds: The Power of Social Networking and New Media on Child Socialization in Oman - Al-Maamari, Wafa; Saleh, Emad Farouk; Helal, Ahmed T; Mostafa, Magdy M.; El-Rawas, Anwar (Current Progress in Arts and Social Studies Research Vol. 6, 2024)
This chapter addresses one of the most significant and contemporary issues: the role of Social Networking and New Media in reshaping the socialization process of children in the Sultanate of Oman. To provide a deep and thorough discussion, the chapter draws upon a scientific study that highlighted both the positive and negative effects of these new media on key dimensions such as language, identity, values, and religious practices. In addition, the chapter presents essential concepts like new media, the Internet, social networks, and socialization, alongside related sub-concepts that influence these dimensions. The goal is to offer a comprehensive understanding of how new media impacts the social and cultural development of Omani children. This analysis builds on previous research conducted by the authors, an exploratory study that employed a descriptive approach and gathered field data through a social survey. The survey was administered to a sample of 270 students from nine primary schools in Muscat. The findings of the study revealed many important insights into how new media influences students' socialization, providing valuable recommendations and perspectives for educators, policymakers, and researchers who are focused on the evolving role of new media in children's socialization.